Teaching pedagogical management and instrumental execution in students of a Higher School of Artistic Training - De La Cruz Bautista, Edwin (2017)
The present research aims to know the relationship between the variables: Teaching pedagogical management and instrumental execution in students of a Higher School of Artistic Training. It is a research of descriptive - correlational level that seeks to find the relationship that exists between both variables. The sample of the study was formed by 30 students of the symphonic band to whom two instruments were applied. Questionnaire for pedagogical management and a checklist for instrumental performance in the symphonic band. The results of the research showed that Spearman's correlation formula had a significance level of 5%, with a significant correlation of Rho = 0.843; For which it is determined that very good pedagogical management of teachers produces very good instrumental performance of the symphonic band in the population under study. Specifically when analyzing the results of the first and second hypotheses specific cognitive and procedural competence of the teacher in relation to the instrumental execution was found a moderate correlation, in the third and fourth specific hypothesis attitudinal and didactic competence of the teacher in relation to the execution Instrumental we found a good correlation level. Concluding that there is a significant correlation between the variables teaching pedagogical management and instrumental execution.